Tax Avoidance in the Energy Sector: The Impact of Transfer Pricing, Firm Size, and Inventory Intensity - Inaya, Mujibatul; Darmansyah, Maman (Indonesian Financial Review, 2025)
This study aims to examine and empirically test the effects of transfer pricing, firm size, and inventory intensity on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2020 to 2024. This research employs a quantitative method using secondary data in the form of financial statements. The population in this study consists of 40 energy sector companies listed on the IDX from 2020 to 2024. The sampling technique employed is purposive sampling, involving 15 companies over 5 years, resulting in a total of 75 data samples. The analysis technique applied is panel data regression analysis, using Eviews 12 software. The results show that transfer pricing, firm size, and inventory intensity simultaneously have a significant effect on tax avoidance. However, partially, transfer pricing has no significant effect on tax avoidance, firm size has a significant effect on tax avoidance, and inventory intensity does not have a significant effect on tax avoidance.